The Effect of E-Learning as One of the Information Technology-Based Learning Media on Student Learning Motivation - Andi Widiyanto; Nugroho Agung Prabowo; Nuryanto Nuryanto; Mochammad Ircham Nashif Amarullah; Arsyad Soni Nuruzzaman (International Journal of Informatics and Information Systems, 2021)
The teaching and learning process is a process that involves participants and educators. The teaching and learning process will be successful if there is interaction between the two parties. Along with the development of information technology, especially the internet in information systems, the teaching and learning process has utilized information technology both from elementary, secondary and higher education levels. Especially for higher education which requires students to be more independent and active in the learning process, information technology is considered very helpful for students. As one of the information technology-based universities, STIKOM Bali utilizes e-learning to support the learning process. Lecturers and students are required to use and utilize e-learning as a means to share information related to lecture materials, assignments, quizzes, discussion forums and others. One of the goals of implementing e-learning in lectures is to increase student learning motivation so that learning achievement will be better. It is also hoped that students will be more interested in the lecture process. One of the things that affect student learning motivation is learning media. The learning media referred to in this study is e-learning learning media. The long and stable application of e-learning at STIKOM Bali is thought to be one of the drivers of student learning motivation. The research method used in this research is problem definition, data collection, data analysis and conclusion drawing. Based on the results of hypothesis testing with H1 hypothesis regression with a significance value of 0.000 and a t-count of 4.015 proven, so that it is concluded that according to STIKOM Bali students e-learning affects student learning motivation.